Dampak Kebijakan Pengelolaan Sampah Sebagai Parameter Kinerja Pemerintah Dalam Bidang Lingkungan Hidup - Toif Fadzoli; Rahayu Subekti; Waluyo Waluyo (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2023)
Law No. 18 of 2008 on Waste Management is an example of the government’s efforts to protect the environtment by managing waste in an integrated and comprehensive manner. The waste generation that is getting out of control and the lack of public knowledge to manage waste is one of the unresolved problems. This study uses empirical legal research methods that are descriptive and through a qualitative approach. The type of data used is secondary data sourced from literature studies. The data collection techniques used in this research were document studies, observations and interviews. The results of this study are that waste management such as waste recycling by the community cannot fully run optimally, this can result in the amount of waste generation increasing from year to year. Obstacles in controlling waste generation due to the absence of specific standards in limiting the amount of waste generation, besides that there are still many landfills that do not meet the standards set by the government. The government in conveying information about waste management to the public has not been fully optimal, the government and the community should work together to build communication to find solutions to waste problems.